Role of percutaneous posterior tibial nerve stimulation either alone or combined with an anticholinergic agent in treating patients with overactive bladder - Kizilyel, Sadik; Karakeci, Ahmet; Ozan, Tunc; Unus, Ihsan; Barut, Osman; Onur, Rahmi (Aves, 2015)
Objective: To evaluate the efficacy of percutaneous tibial nerve stimulation (PTNS), either alone or combined with an anticholinergic agent, in treating patients with an overactive bladder (OAB) in whom previous conservative treatment failed. Material and methods: In this study, we included a total of 30 female patients with OAB in whom all conventional therapies failed between January 2010 and April 2011. Patients were randomly divided into three groups: Group 1, PTNS group; Group 2, patients receiving an anticholinergic agent; and Group 3, patients receiving both PTNS and anticholinergic agent. PTNS treatment continued for 12 weeks with each session lasting 30 min. Results: All parameters of the bladder diary significantly improved in all groups (p<0.05). Similarly, all scores measured by questionnaires (UDI-6, IIQ-7, and OABSS) revealed significant improvements in all groups. When the improvements in symptoms were compared among the groups, there was a statistically significantly higher improvement in groups 1 and 3 than in Group 2. Conclusion: PTNS is a safe, simple, and minimally invasive treatment modality in patients with OAB, and it may be suggested either alone or in combination with anticholinergics when conventional treatments fail.
Aşırı aktif mesaneli hastaların tedavisinde, tek başına ve antikolinerjik ajanla kombine edilerek kullanılan perkütan posterior tibial sinir uyarımının rolü
Keywords: Anticholinergic; overactive bladder; percutaneous tibial nerve stimulation; treatment